PENDIDIKAN INTELEKTUAL DALAM PERSPEKTIF ALI IBN ABI THALIB - Islahudin Islahudin; Muhajir Muhajir (QATHRUNÂ, 2021)
This study aims to determine the intellectual education of Ali bin Abi Thalib. The research method uses data collection techniques in the form of studying and collecting data through reading materials sourced from primary books and secondary books related to the themes discussed. This type of research is qualitative with library research, namely collecting data or scientific papers from the library, and analyzing it with content analysis. The results of his research are that the purpose of education is to humanize humans and deliver them to true happiness (al-sa'adah al-abadiyah). The curriculum used is an educational curriculum that is not much different from the curriculum of the Prophet Muhammad. The educational method used is sima'ah, which is a method that emphasizes the listening dimension, siyahah, which is an observation method based on wandering experience and siyadah, is a method of instilling authority in the realm of leadership.